Adopting seven-day working in practice: a report by the Royal College of Physicians and Surgeons of Glasgow. Issue 4 (November 2014) - Scott, HR; Isles, CJ; Fisher, BM; Long, J; Dunn, FG
Following the UK Academy of Medical Royal Colleges Report on seven day consultant present care, the Royal College of Physicians and Surgeons of Glasgow held a symposium to explore clinicians' views on the ways in which clinical care should best be enhanced outside 'normal' working hours. In addition, a survey of members and fellows was undertaken to identify the tests which would make the greatest impact on care out of hours. Key messages were: (a) that seven-day consultant delivered care would not achieve the desired benefit to patient care if introduced in isolation from other inter-relating factors. These include alternatives to hospital admission, enhanced nursing support, increased junior medical, pharmacy, social care and ambulance availability and greater access to selected diagnostic services; (b) that the care of hospital inpatients is a service which is one part of the totality of secondary care provision. Any significant change in the deployment of staff for inpatient care must be carefully managed so as not to result in a reduced quality of care provided by the rest of the system.